Energy analysis methodology for assessing environmental impacts. - National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 1979)
"An NCHRP staff digest of the essential findings from the final report on NCHRP Project 20-11B, "Toward Environmental Benefit/Cost Analysis: Energy-flow Analysis (Manual)," by M. J. Lavine, T. J. Butler, and A. H. Meyburg, Center for Environmental Research, Cornell University , Ithaca, NY."
Caption title.
At head of title: National Cooperative Highway Research Program.
June 1979.
Keywords: Highway research -- United States